Development of a multi-epitope vaccine candidate for leishmanial parasites applying immunoinformatics and in vitro approaches - Jyotisha,; Qureshi, Rahila; Qureshi, Insaf Ahmed (Frontiers in Immunology, 2023)
Leishmaniasis is a neglected tropical disease, and its severity necessitates the development of a potent and efficient vaccine for the disease; however, no vaccine has yet been approved for clinical use. This study aims to design and evaluate a multi-epitope vaccine against the leishmanial parasite by utilizing helper T lymphocyte (HTL), cytotoxic T lymphocyte (CTL), and linear B-lymphocyte (LBL) epitopes from membrane-bound acid phosphatase of Leishmania donovani (LdMAcP). The designed multi-epitope vaccine (LdMAPV) was highly antigenic, non-allergenic, and non-toxic, with suitable physicochemical properties. The three-dimensional structure of LdMAPV was modeled and validated, succeeded by molecular docking and molecular dynamics simulation (MDS) studies that confirmed the high binding affinity and stable interactions between human toll-like receptors and LdMAPV. In silico disulfide engineering provided improved stability to LdMAPV, whereas immune simulation displayed the induction of both immune responses, i.e., antibody and cell-mediated immune responses, with a rise in cytokines. Furthermore, LdMAPV sequence was codon optimized and cloned into the pET-28a vector, followed by its expression in a bacterial host. The recombinant protein was purified using affinity chromatography and subjected to determine its effect on cytotoxicity, cytokines, and nitric oxide generation by mammalian macrophages. Altogether, this report provides a multi-epitope vaccine candidate from a leishmanial protein participating in parasitic virulence that has shown its potency to be a promising vaccine candidate against leishmanial parasites.